2020
DOI: 10.21203/rs.2.23080/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analysis of physic nut MADS-box gene family and functional characterization of the JcMADS05 gene in transgenic rice

Abstract: Background: Physic nut (Jatropha curcas), a non-edible oilseed plant, is among the most promising alternative energy sources because of its high seed oil content, rapid growth and extensive adaptability. Proteins encoded by MADS-box genes are important transcription factors involved in the regulation of plant growth, seed development and responses to abiotic stress. However, there has been no in-depth research on the MADS-box genes and their roles in physic nut. Results:In the present study, 63 MADS-box genes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…MADS-box genes are expressed in various parts of plants, and play fundamental roles in developmental control and signal transduction, including ower and seed development, owering time control, fruit ripening regulation, and response to abiotic and biological stresses (Bai et al 2019). For example, MADS-box genes in Physic nut (Jatropha curcas) exhibited signi cant induction or inhibition of expression in response to drought and salt stresses (Tang et al 2020). Previous studies have found that the down-regulated expression of OsMADS26 in rice, enhanced the drought resistance of transgenic plants (Khong et al 2015), and the down-regulated expression of SlMBP8 in tomato also enhanced the resistance of transgenic plants to salt stress (Wencheng et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MADS-box genes are expressed in various parts of plants, and play fundamental roles in developmental control and signal transduction, including ower and seed development, owering time control, fruit ripening regulation, and response to abiotic and biological stresses (Bai et al 2019). For example, MADS-box genes in Physic nut (Jatropha curcas) exhibited signi cant induction or inhibition of expression in response to drought and salt stresses (Tang et al 2020). Previous studies have found that the down-regulated expression of OsMADS26 in rice, enhanced the drought resistance of transgenic plants (Khong et al 2015), and the down-regulated expression of SlMBP8 in tomato also enhanced the resistance of transgenic plants to salt stress (Wencheng et al 2017).…”
Section: Introductionmentioning
confidence: 99%